PENGARUH KURIKULUM DI JEPANG DAN DI INDONESIA TERHADAP KUALITAS PENDIDIKAN - Ratna Putri Widjayanti; Hitta Alfi Muhimmah; Nurul Istiqfaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the Influence of the curriculum in Japan and Indonesia on the quality of education, by looking at the advantages and disadvantanges of each. The educational Curriculum in Japan is known to be superior with is systematic and structured approach, paying attention to affective, cognitive and psychomotor aspects, emphasizing discipline, work ethics, manners, etiquette and instilling normative values from an early age and deep understanding of the subject matter. The advantages of this system are the high academic achievement of Japanese students and the formation of strong characters in terms of responsibility and independence. However, disadvantanges include high academic pressure and a lack of student creativity due to a highly standardized approach. On the other hand, the educational vcurriculum in Indonesia shows greater flexibility and diversity, allowing for local adaptation and the application of various teaching methods. The advantages of this system include the development of social skills and cultural diversity, as well as the potential for educational innovation. However, the challenges faced include a lack of consistency and standardization, disparities in the quality of education between regions, this is due to unequal distribution of access to educational facilities and infrastructure as well as the lack of availability of skilled teaching staff. Through this comparison, this article provides insight into how the strengths and weaknesses of each education system can complement each other, offering potential improvements to improve the quality of education in both countries.